Immunohistological study of granulovacuolar degeneration using monoclonal antibodies to neurofilaments. Issue 9 (September 1985) - Kahn, J; Anderton, B H; Probst, A; Ulrich, J; Esiri, M M
Abstract : Neurons undergoing granulovacuolar degeneration have been examined in paraffin sections with three monoclonal antibodies to neurofilaments. Two of these antibodies (BF10, RT97) had been shown previously to react with neurofibrillary tangles. One of these antibodies (RT97) reacted with granular component of granulovacuolar degeneration. BF10 sometimes reacted with the surrounding neuronal cytoplasm. Granulovacuolar degeneration was also detected in a few cells of the anterior olfactory nucleus.